Relationship Between Soil Apparent Electrical Conductivity and Selected Soil Properties, and Oil Palm Yield - Nasir, Jamaluddin (2006)
The ultimate goal of precision farming is to manage the farm on a site specific basis. In realizing this goal, knowledge of the soil and crop characteristics on a practical fine grid basis is necessary. However, to obtain soil and crop parameters on a greater intensity in oil palm plantation using the traditional soil and crop sampling and analysis methods are very expensive, tedious, and time consuming. This problem could be addressed using sensors that can gather information on-the-go. A sensor that is currently available with the above feature is Veris® 3100 soil EC sensor (Electrical Conductivity sensor), a product of Technologies and Probe Systems, Kansas, USA. An evaluation of the sensor was conducted in a mature oil palm plantation at Dusun Durian Estate, Banting, Selangor with the following objectives : (i) To determine the relationships between Veris soil EC and selected soil chemical and physical properties, and oil palm yield, (ii) To investigate the spatial variability of soil EC, selected soil chemical and physical properties, and oil palm yield, and (iii) To define spatial classes of the variables based on interpretation of geostatistical parameters.